2018
DOI: 10.1002/rth2.12067
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of two mutations in von Willebrand disease 2M phenotype

Abstract: Essentials Compound heterozygosity causes a VWD2M phenotype in a child with severe bleeding symptoms.p.P1648fs*45 changes the folding of A2 domain altering VWF binding to GPIbα and type VI collagen.p.P1648fs*45 was considered as an apparent de novo mutation; AS‐PCR revealed paternal mosaicism.Bleeding score and DDAVP's response were worse than those seen in VWD2M heterozygous controls. BackgroundType 2M von Willebrand disease (VWD2M) is usually characterized by VWF:RCo/VWF:Ag<0.6 and normal multimeric profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It was reported that the combination of several genetic variants in the VWF gene could modify the phenotype. 12,62,63 Overall, a strong phenotype-genotype correlation was observed in our cohort of patients, except in one patient whose genotype did not correlate with her type 2A VWD phenotype, probably due to the combined effect of the presence of p.P1266Q described as type 2M VWD and type 2B VWD, p.L1603P, as type 1 VWD and type 2A VWD phenotype, and the novel variant p.R1379H, which showed a nondefined phenotype.…”
Section: Phenotype-genotype Discordancesmentioning
confidence: 54%
“…It was reported that the combination of several genetic variants in the VWF gene could modify the phenotype. 12,62,63 Overall, a strong phenotype-genotype correlation was observed in our cohort of patients, except in one patient whose genotype did not correlate with her type 2A VWD phenotype, probably due to the combined effect of the presence of p.P1266Q described as type 2M VWD and type 2B VWD, p.L1603P, as type 1 VWD and type 2A VWD phenotype, and the novel variant p.R1379H, which showed a nondefined phenotype.…”
Section: Phenotype-genotype Discordancesmentioning
confidence: 54%
“…Genetic variants associated with type 2 VWD are clustered particularly in exons 17, 18, 20 and 28 of VWF gene as reported in ISTH‐SSC VWF Online Database (http://www.ragtimedesign.com/vwf/mutation/) and in EAHAD Coagulation Factor Variant Databases (https://grenada.lumc.nl/LOVD2/VWF/home.php?select_db=VWF). Few reports have investigated the molecular genetics of type 2 VWD of which most included Caucasian patients. The spectrum of variants in other populations is mostly unknown.…”
Section: Introductionmentioning
confidence: 99%